Management of Gastroesophageal reflux disease in adult: Review article - Ramin Niknam; Mohammad Reza Fattahi; Alireza Manafi; sahar khazforoosh; laleh mahmoudi (Shiraz University of Medical Sciences, 2015)
Gastroesophageal reflux disease (GERD) is a very common disease. This review focuses on the management strategies for patients with this disease. We review the initial and maintenance therapy of GERD. We also review different management of recurrent and refractory GERD.